Interfaces frente à morte: atuação ambulatorial de psicólogos e psiquiatras em relação à finitude - Dalmolin, Anaíse (2014)
Talking about death never has been an easy matter. Through historical analysis, one realizes that the fear of death was always present, but with different ways of dealing with it. Today we realize the institutionalization of the dying process, as well as the feelings manifestation. After the Psychiatric Reform, also emerged the Institutions of support in Mental Health, such as Outpatient Mental Health and Psychosocial Care Centers (CAPS), which aim to promote and expand health care to the population in general, in order to promoting wellness and avoid the emergence of chronicity of psychopathology. In these institutions, two specialties professionals stand out in joint action; psychologists and psychiatrists. This mutual action is interesting because it allows a comprehensive view of the subject, in their physical and psychological behavior aspects. Thus, the aim of this study is to understand the presence of death in the outpatient work through the perception of the professionals who work in these places. For this, a qualitative and exploratory study was conducted through semi-structured interviews with guiding principles. For data analysis, was employed content analysis, with emerging categories from the speeches. Among the results, was found several ways of encounter the issue at the clinic, they are: bereavement, complicated grief, preparation for an upcoming death through illness or old age, death and suicidal ideation in life, represented by loss of subjectivity. Among these ways, suicide presented special mention, being described as the most complex due to the large responsibility that the professional has in conducting such cases. Furthermore, was possible to explore the understanding of the professionals in this demand and what were the everyday practices of coping. The study findings are presented in three articles, divided by the subject to which they relate.